Teknik Pemeriksaan MRI Soft Tissue Leher Dengan Klinis Liposarkoma Di Instalasi Radiologi Maya Pada Hospital Jakarta Selatan - I Ketut Narte Astape; Ni Putu Rita Jeniyanti; Andri Setiawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Soft Tissue Neck MRI Examination Technique With Liposarcoma Clinical At The Mayapada Hospital Installation, South Jakarta. MRI examination techniques have a very important role in the medical field because of their ability to produce visual images of the body's soft tissue and metabolic processes. Liposarcoma is a malignancy of mature fat cells in the connective tissue space1. Liposarcoma is the most common type of soft tissue sarcoma, appearing slowly, enlarging, painless, non-ulcerated submucosal mass in middle-aged people, some lesions grow rapidly and become ulcerated early, Liposarcoma is a rare malignant tumor. The purpose of this examination is to find out whether the image results produced using the sequence at Mayapada Hospital can produce a firm image in confirming the diagnosis of liposarcoma. This research is a qualitative study with a case study method using 3 patients who underwent an MRI examination of neck soft tissue with clinical liposarcoma. Data was collected using observation, documentation and interviews with radiographers and radiologists. The results of the data that have been collected can be concluded that the results of the soft tissue MRI examination of the neck with clinical liposarcoma carried out at Mayapada Hospital, South Jakarta are good in confirming the diagnosis and the results of a more detailed anatomical picture.